ANALISIS KANDUNGAN LOGAM BERAT MERKURI (Hg) DAN TIMBAL (Pb) PADA KOSMETIK LIPSTIK YANG BEREDAR DI KOTA MAKASSAR DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Nurmaya Effendi; Mamat Pratama; Husna Kamaruddin (As-Syifaa Jurnal Farmasi, 2014)
Lipstick is a lip cosmetic that almost every day is used by the most women. Lipstick should be safe and does not contain hazardous materials as it can go ingested with food or drink consumed. One of hazardous contaminants in lipstick is contained heavy metals, such as lead and mercury. Based on these considerations, the cosmetic lipstick should be safe and do not contain harmful ingredients, One of the parameters to determine the lipstick cosmetics are safe or not from the content of the metals in contained. To determine the metals Pb and Hg contamination in cosmetics lipsticks do research by doing destruction samples and proceed with the analysis of the metal content using atomic absorption spectrophotometry. The results showedthat inallfour samplesstudiedlipstickall containmercury(Hg) levelseachwithA0.0460 µg/g, B0.0425 µg/g, C0.0345 µg/g, andD0,0431 µg/g, as wellasfor lead(Pb) levelseachwithA6.1628 µg/g, B3.5041 µg/g, C56.6496 µg/g, andD6.0324 µg/g.